Integration of Artificial Intelligence and Project-Based Learning Models in Designing Speech Act Comprehension Test Instruments - Aurel Gracia; Tressyalina (Jurnal Pembelajaran Bahasa dan Sastra, 2026)
This study is a Research and Development (R&D) aimed at developing a speech act comprehension test instrument based on the integration of Artificial Intelligence (AI) and the Project-Based Learning (PJBL) model for students of the Indonesian Language and Literature Education Study Program (PBSI), Faculty of Language and Arts (FBS), Universitas Negeri Padang (UNP). The development of the test instrument followed the 4D model (define, design, develop, and disseminate), conducted up to the develop stage, which included student needs analysis through questionnaires and interviews, instrument design (pre-test, AI- and PJBL-based project assignments, post-test), and validation by experts in learning, linguistics, and graphic design. The instrument was designed in accordance with constructivist principles, emphasizing active student engagement in knowledge construction through projects and contextual activities. The results of the study indicate that the instrument’s content feasibility reached 77.5% (valid category), language feasibility 84.61% (very valid category), and graphical feasibility 88.46% (very valid category), with an overall validity score of 83.52% (very valid). These findings confirm that the integration of AI and the PJBL model in the speech act comprehension test instrument is suitable for evaluating students’ speech act comprehension in a contextual, applicative, and collaborative manner, while also functioning as a pragmatic learning medium that supports analysis, application, and student reflection.